Gambaran Tingkat Personal Hygiene saat Menstruasi pada Remaja Didaerah Kekeringan Desa Tawang Kabupaten Sukoharjo - Indri Magfiroh Rahmawati; Eska Dwi Prajayanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Drought is an event in an area that experiences water scarcity at a certain time which is caused by a certain event. According to BNPB (2023), Central Java Province ranks first in drought disasters with 24 areas in Central Java experiencing drought disasters. According to BPBD, Sukoharjo Regency is one of the areas experiencing drought, one of which is Weru District, Tawang Village. The impact of the drought disaster has resulted in problems in the economic, social health and education sectors. One of the impacts of the drought disaster in the health sector is a decrease in the level of personal hygiene in teenagers during menstruation. The aim of this research was to determine the level of personal hygiene during menstruation among adolescents in drought areas in Tawang Village, Sukoharjo Regency. This research method uses a quantitative descriptive method with a sample size of 73 respondents and uses random sampling techniques. The results of the research showed that the personal hygiene level of the majority of respondents was moderate, as many as 40 respondents (54.8%). The conclusion is that the level of personal hygiene during menstruation in teenagers in drought areas is in the moderate category.